Morphological divergence in Indian oil sardine, Sardinella longiceps Valenciennes, 1847– Does it imply adaptive variation?. (15th April 2016) - Sukumaran, S.; Gopalakrishnan, A.; Sebastian, W.; Vijayagopal, P.; Nandakumar Rao, S.; Raju, N.; Ismail, S.; Abdussamad, E. M.; Asokan, P.K.; Said Koya, K. P.; Rohit, P.
Summary: The Indian oil sardine, Sardinella longiceps, is an important pelagic species in Indian waters, and shows divergent morphology while in sympatry. The reasons behind this divergent morphology were investigated using morphometric, genetic and nutritional analyses. Twenty‐one morphometric characters (as percentage of standard length) and eight meristic characters were studied in the three variants to assess whether they are significantly diverged. Distinct clustering of morphotypes was evident in the principal component analysis on log‐transformed ratios of morphological characters with PC1 and PC2, explaining 50.7% and 17.6% of the total morphological variation, respectively. PC1 was highly correlated with the distance from snout to anal origin, depth at dorsal, distance from snout to pelvic and distance from snout to first dorsal. PC2 was highly correlated with head length, caudal width and anal depth. Analysis of similarities (ANOSIM) was conducted using log‐transformed morphometric ratios, with the results showing the clusters to be well differentiated (R = 0.511; P < 0.01). Similarity of percentage analysis (SIMPER) analysis showed that the differences in depth at the dorsal, anal base length, caudal width, distance from pelvic to anal origin, anal depth and eye diameter accounted for 52% of variations between variant 1 and 2. Differences in caudal width, distance from pelvic to anal origin, anal base length, depth at dorsal and anal depth accounted for 56% of the variation between variant 2 and 3. Differences in caudal width, eye diameter, anal base length, anal depth, distance from pelvic to anal origin accounted for 50% of the variation between variant 1 and 3. Genetic divergence was not significantly based on mitochondrial cytochrome c oxidase I (COI) or control region sequences. Proximate composition analyses showed significantly high fat content in variants 1&3 and significantly high protein content in variant 2, probably due to dissimilar dietary preferences. The study shows that morphotypes of the Indian oil sardine may be the result of divergent selection and adaptive variations, which need further investigation using a long‐term sampling design.